MXene-doped organic silicon pervaporation dehydration membrane and preparation method thereof

By incorporating MXene two-dimensional nanosheets into the BTESA silicone film, the surface properties and network structure of the film are optimized, and the problems of low factors and narrow applicable systems in the separation of alcohol/water mixtures are solved, achieving higher separation performance and a wider range of application.

CN119524628AActive Publication Date: 2025-02-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411645363.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-28
Estimated Expiration
2044-11-18

Smart Images

  • Figure CN119524628A_ABST
    Figure CN119524628A_ABST
Patent Text Reader

Abstract

The invention relates to an MXene-doped organic silicon pervaporation dehydration membrane and a preparation method thereof, and provides an MXene-doped organic silicon pervaporation dehydration membrane and a preparation method thereof, an organic silicon membrane is modified by doping an MXene nanosheet in organic silicon sol, and the surface property of the membrane is regulated and controlled by using hydrophilic groups of the MXene nanosheet, so that the MXene-doped organic silicon pervaporation dehydration membrane is prepared. Meanwhile, through regular arrangement of MXene in an organic silicon network, a rapid transmission channel is provided for water molecules, so that the pervaporation separation performance of the membrane is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of membrane material preparation, and in particular relates to a MXene-doped organosilicon pervaporation dehydration membrane and a preparation method thereof. Background Art

[0002] Alcohol / water separation is a key step in energy-intensive production. The main separation technologies currently include special distillation (azeotropic distillation, extractive distillation), molecular sieve adsorption, and membrane separation (pervaporization). As a branch of membrane separation technology, pervaporation has the advantages of low energy consumption, environmental friendliness, small footprint, and mild operating conditions. It is considered to be an ideal choice for the chemical and energy industries to replace traditional separation technologies (such as distillation, adsorption, etc.). In addition, pervaporation is not limited by vapor-liquid equilibrium and has great advantages in the separation of azeotropic mixtures. Organic silicon materials combine the excellent properties of organic and inorganic components, and have the advantages of high specific surface area, adjustable pore size, good hydrothermal stability, and excellent chemical resistance. They are widely used in gas separation, organic solvent separation (reverse osmosis, pervaporation, nanofiltration, etc.), etc., but have not yet been industrialized. With the further study of organic silicon membranes, in order to meet the needs of various separation systems and further improve the separation performance of membranes, various modification strategies for organic silicon membranes have emerged in an endless stream. The regulation of membrane pore size by doping modification is a common one. The main problems currently exist are that the separation factor of BTESA organosilicon membrane for pervaporation dehydration of alcohol / water mixture is low and the applicable system is narrow. Summary of the invention

[0003] In view of the problem that the BTESA organosilicon membrane has a low separation factor and a narrow applicable system for pervaporation dehydration of alcohol / water mixtures, the present invention proposes to add MXene two-dimensional nanosheets to the BTESA organosilicon sol, and optimize the surface properties and network structure of the organosilicon membrane by utilizing the numerous hydrophilic groups on the MXene surface and the two-dimensional nano-water molecule fast transmission channels that may be formed by the single-layer MXene two-dimensional nanosheets. Thus, a highly selective organosilicon membrane for pervaporation dehydration is prepared.

[0004] MXene is a new type of two-dimensional material that has emerged in recent years. Monolayer MXene has a graphene-like structure, but has richer functional groups and tunable properties than graphene. MXene is usually prepared by selectively etching group A (mainly group IIIA or IVA elements) from the Mn+1AXn phase (n=1, 2 or 3), where M is an early transition metal and X is carbon or. It is worth noting that during the etching and delamination process, rich F, O and OH functional groups are generated on the outer surface of the MXene two-dimensional nanosheet exfoliation layer. Unlike other two-dimensional materials, the functional end groups in MXene do not rely on any controlled reaction, but are generated by the exfoliation process itself. The rich functional groups of MXene can improve the hydrophilicity of the membrane, and the monolayer MXene nanosheets can be regularly stacked to produce a two-dimensional layered structure, in which various Tx groups can create open narrow nanochannels between adjacent MXene nanosheets. These advantages make MXene a promising material for the preparation of efficient separation membranes.

[0005] In order to achieve the purpose of the present invention, the membrane preparation technical scheme of the present invention is as follows:

[0006] A MXene-doped organosilicon pervaporation dehydration and a preparation method thereof, the specific steps are as follows:

[0007] (1) BTESA was used as a silicon source precursor, a MXene single-layer nanosheet solution was added, and hydrochloric acid was used as a catalyst. A hydrolysis polymerization reaction was carried out with water in an ethanol solution at a reaction temperature of 40 °C and a reaction time of 2 h to prepare a BTESA / MXene sol.

[0008] (2) The molar ratio of each component in the organosilica sol is BTESA:H2O:HCl=1:

[0009] 60:0.2, the mass ratio of the organosilicon precursor in the synthesized organosilicon sol is 2.5wt%. (3) Before doping the MXene monolayer nanosheet solution, ultrasonic treatment is required for 1-2h.

[0010] The different mass proportions in the hybrid membranes are named BTESA / MXene-n

[0011] (n=0.1%, 0.2%, 0.3%, 0.5%)

[0012] (4) The BTESA / MXene organosilicon mixed sol is coated on a ceramic support having a silica-zirconia nano-transition layer by a rubbing method, and calcined at 250°C in a nitrogen atmosphere for 30 min. This process is repeated 2-3 times to prepare a BTESA / MXene organosilicon film.

[0013] (5) The silica-zirconia transition layer is prepared by applying silica-zirconia sol on a ceramic support by hot coating, calcining at 550° C. for 15-20 min, and repeating the process 8-12 times.

[0014] (6) The prepared BTESA / MXene hybrid membrane was used for pervaporation dehydration tests of ethanol / water, isopropanol / water, and n-butanol / water systems, and the permeation flux J and separation factor α were used to evaluate the separation performance of the membrane.

[0015] (7) The calculation formulas for permeation flux and separation factor are as follows:

[0016]

[0017] Where J is the total permeate flux (kg m-2h-1), Q is the mass of the permeate (kg), A is the membrane surface area (m2), and t is the permeate time (h). yi and yj are the mass fractions of components i and j in the permeate, and xi and xj are the mass fractions of components i and j in the feed solution.

[0018] The beneficial effects of the present invention are as follows:

[0019] The present invention provides a MXene-doped organosilicon pervaporation dehydration membrane and a preparation method thereof. The organosilicon membrane is modified by doping MXene nanosheets into an organosilicon sol, and the surface properties of the membrane are regulated by utilizing the hydrophilic groups of the MXene nanosheets. Meanwhile, the regular arrangement of MXene in the organosilicon network provides a fast transmission channel for water molecules, thereby improving the pervaporation separation performance of the membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of the pervaporation performance of BTESA membrane and BTESA / MXene-0.2% membrane for different alcohol-water systems at 170°C;

[0021] Figure 2 Schematic diagram of Fourier infrared spectrum of BTESA / MXene hybrid membranes with different MXene nanosheet contents;

[0022] Figure 3 Schematic diagram of water contact angle of BTESA / MXene hybrid membranes with different MXene nanosheet contents;

[0023] Figure 4 Schematic diagram of XRD of BTESA / MXene hybrid membranes with different MXene nanosheet contents;

[0024] Figure 5 Schematic diagram of water vapor adsorption of BTESA / MXene hybrid membranes with different MXene nanosheet contents;

[0025] Figure 6 Schematic diagram of surface electron microscopy of BTESA / MXene hybrid membranes with different MXene nanosheet contents. DETAILED DESCRIPTION

[0026] In order to make the technical features of the present invention more obvious and easy to understand, further detailed description is given below in conjunction with specific embodiments of the present invention.

[0027] Example 1

[0028] (1) 0.5 g of BTESA precursor was uniformly dispersed in 17.95 g of ethanol solution, and a mixed solution of 0.01 g of hydrochloric acid and 1.54 g of water was added at a molar ratio of BTESA: H2O: HCl = 1: 60: 0.2. Then 1 ml of 0.5 mg / ml MXene monolayer nanosheet / ethanol solution was added. The above solution was stirred and reacted in a water bath at 40 ° C for 2 h to obtain a 2.5 wt% BTESA / MXene organosilica sol.

[0029] (3) The above-mentioned BTESA / MXene mixed organosilicon sol was diluted to 0.25wt% with ethanol solvent. To ensure the uniformity of the sol, the mixed sol was ultrasonically dispersed in an ultrasonic machine for 30 minutes before use. The diluted sol was rubbed on the prepared ceramic support with a silica-zirconia nano-transition layer by hot coating, and the coated membrane was calcined in a 250°C tubular furnace with continuous nitrogen for 30 minutes, and this process was repeated 3 times to prepare a BTESA / MXene-0.1% hybrid membrane. The prepared membrane was used for the pervaporation dehydration test of the n-butanol / water system.

[0030] Example 2

[0031] The difference between this embodiment and embodiment 1 is that the doping amount of MXene nanosheets in step 2) is adjusted to 0.2wt%, and the volume of the doped MXene nanosheet solution in step 2) is 2ml. The remaining steps and processes are all referred to embodiment 1 to obtain the film of this embodiment, which is recorded as BTESA / MXene-0.2%.

[0032] Example 3

[0033] The difference between this embodiment and embodiment 1 is that the doping amount of MXene nanosheets in step 2) is adjusted to 0.3wt%, and the volume of the doped MXene nanosheet solution in step 2) is 3ml. The remaining steps and processes are all referred to embodiment 1 to obtain the film of this embodiment, which is recorded as BTESA / MXene-0.3%.

[0034] Example 4

[0035] The difference between this embodiment and embodiment 1 is that the doping amount of MXene nanosheets in step 2) is adjusted to 0.5wt%, and the volume of the doped MXene nanosheet solution in step 2) is 5ml. The remaining steps and processes are all referred to embodiment 1 to obtain the film of this embodiment, which is recorded as BTESA / MXene-0.5%.

[0036] Comparative Example 1

[0037] The difference between this comparative example and Example 1 is that the original BTESA film is prepared without doping with MXene material. BTESA:H2O:HCl=1:60:0.2 is directly heated in a water bath at 40°C for 2h to obtain a BTESA sol, which is diluted to 0.25wt% and coated on a support to obtain a film of this comparative example, which is recorded as the original BTESA film.

[0038] Comparative Example 2

[0039] The only difference between this comparative example and Example 1 is the different coating method, that is, the prepared BTESA / MXene sol is coated on the surface of the support by the immersion pulling method to obtain a BTESA / MXene-0.1% hybrid film.

[0040] Comparative Example 3

[0041] The only difference between this comparative example and Example 1 is the different coating method, that is, the prepared BTESA / MXene sol is coated on the surface of the support by spin coating to obtain a BTESA / MXene-0.1% hybrid film.

[0042] Comparative Example 4

[0043] The steps of this embodiment are basically the same as those of embodiment 1, the only difference being that the BTESA precursor is replaced with a bis(triethoxysilyl)biphenyl (BTESBPh) precursor.

[0044] The membranes prepared in Examples 1 to 4 and Comparative Example 1 were used for the pervaporation dehydration test of the n-butanol / water system. The specific implementation steps were carried out with reference to the corresponding steps in Separation and Purification Technology, 2024, 344: 12710. The feed liquid composition was: 95% butanol, 5% water. The feed liquid temperature was controlled to be 70°C. The obtained data were recorded in Table 1.

[0045] Table 1 Pervaporation dehydration performance of BTESA / MXene membranes with different MXene doping amounts

[0046] membrane <![CDATA[Total flux (kgm -2 h -1 )]]> Separation factor Example 1 1.21 395 Example 2 1.00 716 Example 3 1.85 370 Example 4 2.14 213 Comparative Example 1 1.85 171

[0047] It can be seen from Table 1 that with the increase of MXene doping amount, the flux of BTESA / MXene mixed matrix membrane first decreases and then increases, and the separation factor first increases and then decreases. When the MXene doping amount is between 0.1wt% and 0.3wt%, the separation factor of BTESA / MXene increases and the permeation flux decreases. According to the dissolution-diffusion mechanism, the increase in separation factor mainly comes from the increase in dissolution selectivity and diffusion selectivity. MXene has good hydrophilicity, which can be seen in the characterization of water contact angle test. It has been reported that the higher the hydrophilicity, the more conducive to water adsorption. The doping of hydrophilic MXene increases the hydrophilicity of the membrane, allowing water to preferentially permeate the membrane, that is, the dissolution selectivity increases. In addition, the presence of interlayer nanochannels of MXene limits the diffusion of water molecules, almost does not allow n-butanol to pass through, and improves the diffusion selectivity of the membrane, so the separation factor increases. However, at the same time, the doped MXene will increase the transmission path of the permeating molecules, and the flux will also decrease while improving the selectivity. When the doping amount of MXene is further increased, affected by the inherent compatibility problems of the mixed matrix membrane, MXene agglomerates on the membrane surface to form non-selective defects, resulting in a decrease in the separation factor and an increase in the permeation flux.

[0048] The application system of BTESA / MXene-0.2 mixed matrix membrane with good separation performance was expanded to (95 / 5wt%) ethanol / water system and (95 / 5wt%) isopropanol / water system. Its pervaporation performance is as follows Figure 1 As shown. Figure 1 It can be seen that compared with the original BTESA membrane, the separation factors of BTESA / MXene-0.2% for ethanol / water, isopropanol / water, and n-butanol / water systems have increased significantly, especially for isopropanol and n-butanol systems, where the separation factors increased by 3.4 and 3.2 times, respectively. The flux of the ethanol / water system is not as good as the other two systems, probably because the molecular size of ethanol molecules is relatively small and they can form clusters with water to pass through the membrane, increasing the difficulty of separation.

[0049] Referring to the aforementioned application method, the flux and separation factor of the membranes prepared in Comparative Examples 1-4 were measured at 70°C. The results are shown in Table 2.

[0050] Table 2 Pervaporation dehydration performance of different membranes for n-butanol / water (95 / 5wt%) system.

[0051] membrane <![CDATA[Total flux (kgm -2 h -1 )]]> Separation factor Example 1 1.21 395 Comparative Example 1 1.85 171 Comparative Example 2 1.16 459 Comparative Example 3 1.42 324 Comparative Example 4 1.63 286

[0052] As shown in Table 2, the coating method has a great influence on the separation performance of the BTESA / MXene hybrid membrane. This is because the membrane thickness and uniformity prepared by different coating methods are different. In addition, the choice of precursor also affects the separation performance of the hybrid membrane. BTESBPh has a larger specific surface area and higher flux due to its large steric hindrance phenyl group. However, due to its larger pore size structure, the screening effect on molecules is weakened and the separation factor decreases.

[0053] Many specific details are set forth in the description of the above embodiments to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed above.

[0054] Secondly, the so-called "one embodiment" or "embodiment" refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0055] In summary, the present invention provides a MXene-doped organosilicon pervaporation dehydration and a preparation method thereof. The present invention selects a high specific surface area organosilicon material BTESA with a rigid acetylene bridge as a precursor, and incorporates hydrophilic MXene two-dimensional nanosheets therein. By constructing a two-dimensional nanochannel, the diffusion selectivity of water molecules is improved, thereby achieving the purpose of improving the BTESA / MXene membrane separation factor. By optimizing the composite ratio, a composite membrane material with optimal separation performance is obtained. The optimized membrane is used for alcohol / water solution separation in different systems to explore its more possible applications.

Claims

1. A MXene-doped organosilicon pervaporation dehydration and a preparation method thereof, characterized in that: The specific steps of the preparation method are as follows: (1) BTESA was used as a silicon source precursor, a MXene single-layer nanosheet solution was added, and hydrochloric acid was used as a catalyst to carry out a hydrolysis polymerization reaction with water in an ethanol solution at a reaction temperature of 40°C and a reaction time of 2 h to prepare a BTESA / MXene sol; (2) The molar ratio of each component in the organosilica sol is BTESA:H2O:HCl=1: 60:0.2, the mass ratio of the organosilicon precursor in the synthesized organosilicon sol is 2.5wt%; (3) Before doping the MXene monolayer nanosheet solution, it is necessary to ultrasonicate for 1-2 h. The membranes are named BTESA / MXene-n (n = 0.1%, 0.2%, 0.3%, 0.5%) according to the different mass proportions of MXene in the hybrid membranes. (4) coating the BTESA / MXene organosilicon mixed sol on a ceramic support having a silica-zirconia nano-transition layer by a rubbing method, calcining at 250° C. in a nitrogen atmosphere for 30 min, and repeating this process 2-3 times to prepare a BTESA / MXene organosilicon film; (5) wherein the silica-zirconia transition layer is prepared by applying silica-zirconia sol on a ceramic support by hot coating, calcining at 550° C. for 15-20 min, and repeating the process 8-12 times; (6) The prepared BTESA / MXene hybrid membrane was used for pervaporation dehydration tests of ethanol / water, isopropanol / water, and n-butanol / water systems, and the permeation flux J and separation factor α were used to evaluate the separation performance of the membrane; (7) The calculation formulas for permeation flux and separation factor are as follows: Where J is the total permeate flux (kg m-2h-1), Q is the mass of the permeate (kg), A is the membrane surface area (m2), and t is the permeate time (h). yi and yj are the mass fractions of components i and j in the permeate, and xi and xj are the mass fractions of components i and j in the feed solution.

Citation Information

Patent Citations

  • Preparation method of organosilicon film and application of organosilicon film in pervaporation treatment of high-salinity wastewater

    CN106110909A

  • Preparation method of organic silicon film for separating CO2 / N2

    CN113648855A

  • Method for preparing blend membrane by homogeneous regulation and control of two-dimensional material-organic silicon

    CN115738764A

  • Preparation method of graphene oxide reverse osmosis membrane and graphene oxide reverse osmosis membrane

    CN117018876A

  • MOF-74 / biphenyl bridge organic silicon hybrid membrane as well as preparation method and application thereof

    CN117463173A